2000
DOI: 10.1007/s001980050006
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Longitudinal Changes in Quantitative Ultrasound with Dual-Energy X-ray Absorptiometry: The Four-Year Effects of Hormone Replacement Therapy

Abstract: Quantitative ultrasound (QUS) has been proposed as a tool which can measure both the quantitative and qualitative aspects of bone tissue and can predict the future risk of osteoporotic fractures. However, the usefulness of QUS in long-term monitoring has yet to be defined. We studied a group of early postmenopausal women over a 4-year period. Thirty subjects were allocated to hormone replacement therapy and 30 selected as controls matched for age, years past the menopause (YPM) and bone mineral density (BMD) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
4

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 27 publications
1
26
0
4
Order By: Relevance
“…It is vital to keep in mind that BMD changes in peripheral bones such as phalanx and forearm must be very carefully interpreted, taking this phenomenon into consideration. Changes expected in BUA, SOS or even in the index calculated with these two parameters are far smaller and slower than BMD variations as measured by central DXA (23). While with DXA of the hip, 30% BMD loss is expected from 50 to 70 years of age, only 5 to 15% are observed when ultrasound peripheral technologies are used.…”
Section: Potential Application #4: Monitoring Changes Over Timementioning
confidence: 86%
“…It is vital to keep in mind that BMD changes in peripheral bones such as phalanx and forearm must be very carefully interpreted, taking this phenomenon into consideration. Changes expected in BUA, SOS or even in the index calculated with these two parameters are far smaller and slower than BMD variations as measured by central DXA (23). While with DXA of the hip, 30% BMD loss is expected from 50 to 70 years of age, only 5 to 15% are observed when ultrasound peripheral technologies are used.…”
Section: Potential Application #4: Monitoring Changes Over Timementioning
confidence: 86%
“…[148][149][150][151][152][153][154][155][156][157][158][159][160][161][162][163][164] It has been observed that changes in heel QUS parameters, especially the stiffness index (SI), do mimic the treatment response observed in BMD. In two studies involving alendronate, for example, the Achilles SI was observed to significantly increase with treatment over time.…”
Section: ) Using Qus To Monitor Osteoporosis Treatmentmentioning
confidence: 99%
“…[26][27][28] The precision of QUS is generally reported to be poorer than that of DXA. There are currently QUS devices available for measuring a range of anatomical sites including both predominantly trabecular and predominantly cortical bone sites.…”
Section: Precisionmentioning
confidence: 99%
“…10,105,106 However, Sahotal et al found a positive effect of HRT at the calcaneus in a longitudinal study over a four year period, although the individual increases for BUA and SOS were not as great as found for lumbar spine and total hip BMD. 26 A number of longitudinal studies have demonstrated a response of QUS to patients treated with bisphosphonates at the calcaneus and tibia. [107][108][109][110] However, as a result of the poorer precision, the follow-up period is generally required to be longer than that of DXA.…”
Section: Monitoring Therapymentioning
confidence: 99%